Colonization history of Metrioptera roeselii in northern Europe indicates human‐mediated dispersal. (14th December 2012) - Kaňuch, Peter; Berggren, Åsa; Cassel‐Lundhagen, Anna; Bush, Mark
Abstract Aim The bush‐cricket Metrioptera roeselii is an example of an insect which has expanded its indigenous range beyond expectations based on its natural dispersal potential. Understanding how species colonize new areas is vital for formulating effective species conservation programmes and managing invasive species. The aim of this research is to use mitochondrial sequence and microsatellite data to delineate the likely origin and dispersal pathways of M. roeselii in northern Europe. The well‐known ecology of the species and the detailed colonization data make it a very suitable model species for addressing questions relating to invasiveness. Location Fennoscandia, Baltic Sea coast, northern Europe. Methods Using a 676 bp fragment of the mitochondrial cytochrome oxidase subunit I (COI) gene and seven polymorphic microsatellite loci, we genotyped and compared populations at 28 sites within the continuous range of M. roeselii along the Baltic Sea coast, and 10 isolated populations in Denmark, islands in the Baltic Sea and the Scandinavian Peninsula. The acquired data, information on the species' ecology and historical population establishment records were used to infer the colonization history and pathways of this species. Results Both mitochondrial DNA and microsatellite data indicated that several of the isolated populations did not originate from their nearest locations within the continuous distribution area of M. roeselii. Instead, the likeliest source populations were in some cases situated > 500 km from the isolated populations. Hence the first records of appearance in the isolated sites did not coincide with the species' natural expansion but agreed well with the time of colonization of the founder sites inferred from the genetic data. Main conclusions The limited ability of M. roeselii to cross geographical barriers through active dispersal, the inferred colonization pathways from this study, and the knowledge that transport of eggs can potentially occur with agricultural products collectively suggest that at least some of the isolated populations originate from human‐mediated introductions rather than natural dispersal.